2015
DOI: 10.1016/j.hrthm.2015.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent protein kinase II (CaMKII) inhibition ameliorates arrhythmias elicited by junctin ablation under stress conditions

Abstract: Background Aberrant calcium signaling is considered as one of the key mechanisms contributing to arrhythmias, especially in the context of heart failure. In human heart failure, there is significant down-regulation of the sarcoplasmic reticulum protein junctin and junctin deficiency in mice is associated with stress-induced arrhythmias. Objective This study was designed to determine whether the increased SR Ca2+ leak and arrhythmias, associated with junctin ablation, may be associated with increased CaMKII a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…In our study, chronic aldosterone infusion decreased SERCA2a protein expression and the phosphorylation of PLB at Thr17 and increased NCX1 protein expression and the phosphorylation of RyR2 but did not alter RyR2 or PLB protein expression. Phosphorylation of PLB at Thr17 site is a specific target of CaMKII, and activated CaMKII is associated with increased phosphorylation of PLB at Thr17 site . However, in our study, the level of phosphorylation of PLB at Thr17 is markedly decreased in the aldosterone‐induced heart, where activated CaMKII was observed, although no apparent change in total PLB abundance.…”
Section: Discussioncontrasting
confidence: 76%
“…In our study, chronic aldosterone infusion decreased SERCA2a protein expression and the phosphorylation of PLB at Thr17 and increased NCX1 protein expression and the phosphorylation of RyR2 but did not alter RyR2 or PLB protein expression. Phosphorylation of PLB at Thr17 site is a specific target of CaMKII, and activated CaMKII is associated with increased phosphorylation of PLB at Thr17 site . However, in our study, the level of phosphorylation of PLB at Thr17 is markedly decreased in the aldosterone‐induced heart, where activated CaMKII was observed, although no apparent change in total PLB abundance.…”
Section: Discussioncontrasting
confidence: 76%
“…Phosphorylation of PLB at T17 site is a specific target of CaMKII and activated CaMKII is generally associated with increased phosphorylation of PLB at T17 site. 39 However, we found that p-PLB (at T17 site) is significantly decreased in the HFD-induced heart, where activated CaMKII was observed, although no apparent change was in total PLB abundance (Fig. 5 ).…”
Section: Discussionmentioning
confidence: 72%
“…Stabilization of RyR2-mediated Ca release can be achieved indirectly by targeting CaMKII, given chronic activity in cardiac disease has been linked to RyR2 channel dysfunction ( Ai et al, 2005 ; Uchinoumi et al, 2016 ; Zhang, 2017 ). It has been demonstrated that blockade of CaMKII and inhibition of RyR2 phosphorylation in cardiac disease improves intracellular Ca 2+ homeostasis and attenuates arrhythmogenesis ( Ather et al, 2013 ; Tzimas et al, 2015 ; Uchinoumi et al, 2016 ), including in a rat model of type 2 diabetes ( Sommese et al, 2016 ), but this is also not a universal finding ( Chakraborty et al, 2014 ). Alternatively, stabilization could be achieved by a reduction of RyR2 oxidation.…”
Section: Therapeutic Strategies To Improve Ca 2+ Hmentioning
confidence: 99%